Answer:
(1,3)
y= 3
x= 1
Step-by-step explanation:
7x+y=10
3x-2y= -3
solve the equation
y=10-7x
3x-2y= -3
substitute the value of y into an equation
3x-2(10-7x)= -3
distribute
3x-20-14x= -3
add 14x from both sides
17x-20= -3
add 20 from both sides
17x=17
divide both sides by 17
x=1
substitute the value of x into an equation
y=10-7•1
multiply 7 to 1
y=10-7
subtract
y=3
(1,3)
Answer: 60
Step-by-step explanation:
Answer:
Exchange and unilateral contract
Step-by-step explanation:
We define what is meant by exchange and unilateral contract as follows.
An exchange contract is a type of contract in which there is an agreement between parties to pay in exchange for a particular performance. Hence, when there is an agreement between two parties in which one solely indicates that he would be paying the other party if the other party delivers on an agreed performance.
Now, we Move on to know what a unilateral contract is. Like the name suggests, a unilateral contract is the decision of a single party. A single party is the one that makes the concessions needed to make work, a unilateral agreement. It is quite different from bilateral where there are inputs from both parties
Answer:
![\large\boxed{\sqrt{xy^3}\cdot\sqrt[3]{x^2y}=\sqrt[6]{x^7y^{11}}}](https://tex.z-dn.net/?f=%5Clarge%5Cboxed%7B%5Csqrt%7Bxy%5E3%7D%5Ccdot%5Csqrt%5B3%5D%7Bx%5E2y%7D%3D%5Csqrt%5B6%5D%7Bx%5E7y%5E%7B11%7D%7D%7D)
Step-by-step explanation:
![\text{Use}\ a^\frac{1}{n}=\sqrt[n]{a}\\\\\sqrt{xy^3}\cdot\sqrt[3]{x^2y}=(xy^3)^\frac{1}{2}(x^2y)^\frac{1}{3}\\\\\text{use}\ (ab)^n=a^nb^n\ \text{and}\ (a^n)^m=a^{nm}\\\\=x^\frac{1}{2}y^{(3)\left(\frac{1}{2}\right)}x^{(2)\left(\frac{1}{3}\right)}y^\frac{1}{3}\\\\\text{use}\ a^na^m=a^{n+m}\\\\=x^{\frac{1}{2}+\frac{2}{3}}y^{\frac{3}{2}+\frac{1}{3}}\\\\\text{the common denominator is 6}](https://tex.z-dn.net/?f=%5Ctext%7BUse%7D%5C%20a%5E%5Cfrac%7B1%7D%7Bn%7D%3D%5Csqrt%5Bn%5D%7Ba%7D%5C%5C%5C%5C%5Csqrt%7Bxy%5E3%7D%5Ccdot%5Csqrt%5B3%5D%7Bx%5E2y%7D%3D%28xy%5E3%29%5E%5Cfrac%7B1%7D%7B2%7D%28x%5E2y%29%5E%5Cfrac%7B1%7D%7B3%7D%5C%5C%5C%5C%5Ctext%7Buse%7D%5C%20%28ab%29%5En%3Da%5Enb%5En%5C%20%5Ctext%7Band%7D%5C%20%28a%5En%29%5Em%3Da%5E%7Bnm%7D%5C%5C%5C%5C%3Dx%5E%5Cfrac%7B1%7D%7B2%7Dy%5E%7B%283%29%5Cleft%28%5Cfrac%7B1%7D%7B2%7D%5Cright%29%7Dx%5E%7B%282%29%5Cleft%28%5Cfrac%7B1%7D%7B3%7D%5Cright%29%7Dy%5E%5Cfrac%7B1%7D%7B3%7D%5C%5C%5C%5C%5Ctext%7Buse%7D%5C%20a%5Ena%5Em%3Da%5E%7Bn%2Bm%7D%5C%5C%5C%5C%3Dx%5E%7B%5Cfrac%7B1%7D%7B2%7D%2B%5Cfrac%7B2%7D%7B3%7D%7Dy%5E%7B%5Cfrac%7B3%7D%7B2%7D%2B%5Cfrac%7B1%7D%7B3%7D%7D%5C%5C%5C%5C%5Ctext%7Bthe%20common%20denominator%20is%206%7D)
![\dfrac{1}{2}=\dfrac{1\cdot3}{2\cdot3}=\dfrac{3}{6}\\\\\dfrac{2}{3}=\dfrac{2\cdot2}{3\cdot2}=\dfrac{4}{6}\\\\\dfrac{3}{2}=\dfrac{3\cdot3}{2\cdot3}=\dfrac{9}{6}\\\\\dfrac{1}{3}=\dfrac{1\cdot2}{3\cdot2}=\dfrac{2}{6}\\\\x^{\frac{1}{2}+\frac{2}{3}}y^{\frac{3}{2}+\frac{1}{2}}=x^{\frac{3}{6}+\frac{4}{6}}y^{\frac{9}{6}+\frac{2}{6}}=x^{\frac{7}{6}}y^{\frac{11}{6}}=\sqrt[6]{x^7y^{11}}](https://tex.z-dn.net/?f=%5Cdfrac%7B1%7D%7B2%7D%3D%5Cdfrac%7B1%5Ccdot3%7D%7B2%5Ccdot3%7D%3D%5Cdfrac%7B3%7D%7B6%7D%5C%5C%5C%5C%5Cdfrac%7B2%7D%7B3%7D%3D%5Cdfrac%7B2%5Ccdot2%7D%7B3%5Ccdot2%7D%3D%5Cdfrac%7B4%7D%7B6%7D%5C%5C%5C%5C%5Cdfrac%7B3%7D%7B2%7D%3D%5Cdfrac%7B3%5Ccdot3%7D%7B2%5Ccdot3%7D%3D%5Cdfrac%7B9%7D%7B6%7D%5C%5C%5C%5C%5Cdfrac%7B1%7D%7B3%7D%3D%5Cdfrac%7B1%5Ccdot2%7D%7B3%5Ccdot2%7D%3D%5Cdfrac%7B2%7D%7B6%7D%5C%5C%5C%5Cx%5E%7B%5Cfrac%7B1%7D%7B2%7D%2B%5Cfrac%7B2%7D%7B3%7D%7Dy%5E%7B%5Cfrac%7B3%7D%7B2%7D%2B%5Cfrac%7B1%7D%7B2%7D%7D%3Dx%5E%7B%5Cfrac%7B3%7D%7B6%7D%2B%5Cfrac%7B4%7D%7B6%7D%7Dy%5E%7B%5Cfrac%7B9%7D%7B6%7D%2B%5Cfrac%7B2%7D%7B6%7D%7D%3Dx%5E%7B%5Cfrac%7B7%7D%7B6%7D%7Dy%5E%7B%5Cfrac%7B11%7D%7B6%7D%7D%3D%5Csqrt%5B6%5D%7Bx%5E7y%5E%7B11%7D%7D)
Answer:
<h3>x = 1 and 2/3 or x = 1 2/3</h3><h3 />
Step-by-step explanation:
Simplify both sides of equation
1 * x = 1 2/3
1 * x is 1x which is the same as x because there is one x
then for the improper fraction which is 1 2/3
to simplify improper fractions we times the whole number by the denominator
so 1 * 3 then add the numerator 2 and the denominator stays the same so we get x = 5/3
now we have x = 5/3 this is not correct because the numerator is bigger than the denominator so we just subtract the denominator from the numerator and how many times 3 goes into 5 (in this case 1) becomes the new whole number.
therefore we get x = 1 2/3